Heart rate reduction after genetic ablation of L-type Cav1.3 channels induces cardioprotection against ischemia-reperfusion injury - Delgado-Betancourt, Viviana; Chinda, Kroekkiat; Mesirca, Pietro; Barrère, Christian; Covinhes, Aurélie; Gallot, Laura; Vincent, Anne; Bidaud, Isabelle; Kumphune, Sarawut; Nargeot, Joël; Piot, Christophe; Wickman, Kevin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Acute myocardial infarction (AMI) is the major cause of cardiovascular mortality worldwide. Most ischemic episodes are triggered by an increase in heart rate, which induces an imbalance between myocardial oxygen delivery and consumption. Developing drugs that selectively reduce heart rate by inhibiting ion channels involved in heart rate control could provide more clinical benefits. The Cav1.3-mediated L-type Ca2+ current (ICav1.3) play important roles in the generation of heart rate. Therefore, they can constitute relevant targets for selective control of heart rate and cardioprotection during AMI. Objective We aimed to investigate the relationship between heart rate and infarct size using mouse strains knockout for Cav1.3 (Cav1.3−/−) L-type calcium channel and of the cardiac G protein gated potassium channel (Girk4−/−) in association with the funny (f)-channel inhibitor ivabradine. Methods Wild-type (WT), Cav1.3+/−, Cav1.3−/− and Girk4−/− mice were used as models of respectively normal heart rate, moderate heart rate reduction, bradycardia, and mild tachycardia, respectively. Mice underwent a surgical protocol of myocardial IR (40 min ischemia and 60 min reperfusion). Heart rate was recorded by one-lead surface ECG recording, and infarct size measured by triphenyl tetrazolium chloride staining. In addition, Cav1.3−/− and WT hearts perfused on a Langendorff system were subjected to the same ischemia-reperfusion protocol ex vivo, without or with atrial pacing, and the coronary flow was recorded. Results Cav1.3−/− mice presented reduced infarct size (−29%), while Girk4−/− displayed increased infarct size (+30%) compared to WT mice. Consistently, heart rate reduction in Cav1.3+/− or by the f-channel blocker ivabradine was associated with significant decrease in infarct size (−27% and −32%, respectively) in comparison to WT mice. Conclusion Our results show that decreasing heart rate allows to protect the myocardium against IR injury in vivo and reveal a close relationship between basal heart rate and IR injury. In addition, this study suggests that targeting Cav1.3 channels could constitute a relevant target for reducing infarct size, since maximal heart rate dependent cardioprotective effect is already observed in Cav1.3+/− mice.